Gender Differences in the Benefits of an Influential Early Childhood Program - Jorge Luis García; James J. Heckman; Anna Ziff (Institute of Labor Economics (IZA), 2017)
This paper estimates gender differences in life-cycle impacts across multiple domains of an influential enriched early childhood program targeted toward disadvantaged children that was evaluated by the method of random assignment. We assess the impacts of the program on promoting or alleviating population differences in outcomes by gender. For many outcomes, boys benefit relatively more from high-quality center childcare programs compared to low-quality programs. For them, home care, even in disadvantaged environments, is more beneficial than lower-quality center childcare for many outcomes. This phenomenon is not found for girls. We investigate the sources of the gender differentials in impacts.
Keywords: J13; I28; C93; 330; gender differences; childcare; early childhood education; health; randomized trials; substitution bias